2016
DOI: 10.3390/md14120219
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of Oil Extracted from Wasted Norway Lobster (Nephrops norvegicus) Heads and Comparison with Oil Extracted from Antarctic Krill (Euphasia superba)

Abstract: Abstract:In the UK, the Norway lobster (Nephrops norvegicus) supports its most important shellfish fishery. Nephrops are sold either whole, or as "tails-only" for the scampi trade. In the "tailing" process, the "head" (cephalothorax) is discarded as waste. A smaller crustacean species, the Antarctic krill Euphasia superba, represents an economically valuable industry, as its extractable oil is sold as a human dietary supplement. The aim of this study was to determine the amount and composition of the oil conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…However, the amounts of PUFAs and ω-3 fatty acids were significantly higher (22.6 vs 31.3%, 50.8 vs 58%) when lipids were recovered from lobster livers using supercritical carbon dioxide (SC-CO 2 ) extraction technique (Nguyen et al 2015 ). Richness of PUFAs and ω-3 fatty acids in lobster lipids is comparable to that of menhaden lipids (Tsvetnenko et al 1996 ) or even higher than that of krill lipids (Albalat et al 2016 ). Particularly, lobster lipids also contain carotenoids and astaxanthin with concentrations of 70.4 and 41.6 μg/mL, respectively (Nguyen 2017 ).…”
Section: Lpbs Containing Several Valuable Componentsmentioning
confidence: 92%
See 3 more Smart Citations
“…However, the amounts of PUFAs and ω-3 fatty acids were significantly higher (22.6 vs 31.3%, 50.8 vs 58%) when lipids were recovered from lobster livers using supercritical carbon dioxide (SC-CO 2 ) extraction technique (Nguyen et al 2015 ). Richness of PUFAs and ω-3 fatty acids in lobster lipids is comparable to that of menhaden lipids (Tsvetnenko et al 1996 ) or even higher than that of krill lipids (Albalat et al 2016 ). Particularly, lobster lipids also contain carotenoids and astaxanthin with concentrations of 70.4 and 41.6 μg/mL, respectively (Nguyen 2017 ).…”
Section: Lpbs Containing Several Valuable Componentsmentioning
confidence: 92%
“…Lobster liver is another lipid-rich part of lobster with the lipid content of which is up to 24.3% (Nguyen et al 2015 ). Among crustaceans, LPBs contain more lipids than crab and shrimp by-products, while this value is comparable to that of krill being used for lipid production (Albalat et al 2016 ). Lobster lipids are rich in PUFAs and ω-3 fatty acids as reported in the study of Tsvetnenko et al ( 1996 ): lipids extracted from lobster cephalothorax contained 22.6% of fatty acids in which ω-3 fatty acids accounted for 50.8%.…”
Section: Lpbs Containing Several Valuable Componentsmentioning
confidence: 98%
See 2 more Smart Citations
“…Lipid content in crustacean by-products may be variable depending on the species, the fishery’s geographical location, and the kind of by-products. Recently, Albalat et al [ 33 ] showed that oil recovered from the head waste of the Norway Lobster ( Nephrops norvegicus ) contains a higher proportion of EPA and DHA (15.0% and 8.3% of total neutral lipids, respectively, than krill oil (4.3% of EPA and 2.3% of DHA)). However, the content and profile of the recovered lipid are subjected to considerable variations according to the geographic location of the fishery and the seasonality.…”
Section: Crustacean By-products As a Source Of Valuable Compoundsmentioning
confidence: 99%